Misconception Analysis Using Three-Tier Mutiple Choice Diagnostic Test Assisted by Google Form on Excretory System Material Class XI Students at SMAN 16 Samarinda - Jailani; Bonita, Tias; Masitah; Nasution, Ruqoyyah (INSTITUT AGAMA ISLAM NEGERI AMBON, 2024)
The situation where there is a mismatch between the student's initial concept and the conception put forward by the expert results in students being very confident in the wrong concept or called a misconception. There are several circumstances that can lead to misconceptions. This study used Three-Tier Multiple Choice diagnostic examination with the help of Google Form to determine the misconceptions and contributing variables held by students of class XI at SMAN 16 Samarinda regarding the material of the excretory system. The researcher used a descriptive research design using a sample of class XI-2 which amounted to 33 students. Based on the results of data analysis, students' concept understanding of the excretory system material is divided into four categories, namely understanding the concept (60%), understanding the concept but not sure (3%), misconceptions (23%), and not understanding (14%). The majority of misconceptions were in the category of questions about urine formation and anatomy and physiology of parts of the excretory system. The average misconception is 23%, the level of student misconceptions is included in the low group. Factors causing misconceptions in students are due to themselves such as students' learning abilities and lack of interest in learning, while from outside themselves such as less conducive classroom conditions, lack of laboratory tools and materials, students who do not dare to ask questions and are not focused, students who still learn overnight, and limited learning time so that the explanation cannot be conveyed in full. Keywords: Misconception, Test Diagnostic Three-Tier Multiple Choice, Google Form